2008
DOI: 10.2174/157488608783333961
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Postpartum Psychosis: Challenges and Opportunities

Abstract: Postpartum psychosis is a rare but serious psychiatric illness that follows delivery. Although controversy continues to surround its diagnostic status, it is generally considered an episode of bipolar disorder with accompanying psychotic features. The consequences of untreated postpartum psychosis can be serious due to the associated risk of suicide and infanticide; however, its close temporal association with childbirth should provide an opportunity to undertake prophylactic measures in women at risk for deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 40 publications
(54 reference statements)
0
11
0
Order By: Relevance
“…22 Mothers with mental disorders were identified using the ICD-10-AM diagnosis codes: (1) schizophrenia, schizophrenia-like disorders including delusional and schizoaffective disorders (F20-F22, F24-F29); (2) (5) anxiety disorders (F40, F41, F42); (6) adjustment disorders (F43); (6) anxiety disorders (F40-F42); (7) personality disorders (F60-F69); and (8) mental illness due to substance use (F10-F19).The ''overall'' group consisted of these eight categories plus the remaining F00-F99 psychiatric diagnoses. In this study, only principal diagnoses that were chiefly responsible for the hospital admission 23 were used for the analysis.…”
Section: Diagnosis Of Mental and Behavioral Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Mothers with mental disorders were identified using the ICD-10-AM diagnosis codes: (1) schizophrenia, schizophrenia-like disorders including delusional and schizoaffective disorders (F20-F22, F24-F29); (2) (5) anxiety disorders (F40, F41, F42); (6) adjustment disorders (F43); (6) anxiety disorders (F40-F42); (7) personality disorders (F60-F69); and (8) mental illness due to substance use (F10-F19).The ''overall'' group consisted of these eight categories plus the remaining F00-F99 psychiatric diagnoses. In this study, only principal diagnoses that were chiefly responsible for the hospital admission 23 were used for the analysis.…”
Section: Diagnosis Of Mental and Behavioral Disordersmentioning
confidence: 99%
“…1,2 It is reported that one in five women experiences a mental health disorder during the postpartum period, with problems ranging from depression, anxiety disorders, posttraumatic stress disorder, and obsessive-compulsive disorder to bipolar disorder, schizophrenia, and psychosis. [3][4][5][6][7][8][9] Mental health problems arising in the perinatal period may become chronic and carry over to future pregnancies. [10][11][12] Maternal mental illness can also have adverse effects on the cognitive, social, and emotional development of infants due to impaired maternal-infant interactions.…”
Section: Introductionmentioning
confidence: 99%
“…6Y9 In mice, it was shown recently that lithium treatment up-regulates FGF-23 formation, an effect paralleled by substantial decrease of serum 1,25(OH) 2 D 3 and phosphate concentrations. 10 The present study explores the effect of lithium treatment on serum FGF-23, 1,25(OH) 2 D 3 , calcium, and phosphate concentrations in depressed patients.…”
Section: Impact Of Lithium Treatment On Fgf-23 Serum Concentrations Imentioning
confidence: 98%
“…8 A few case reports suggest that PP may be treated with lithium or other anticonvulsants and typical antipsychotics. 9,10 Little is known about the efficacy of atypical antipsychotics in PP. 11 Clozapine has been reported to be effective in 1 case report, 11 and olanzapine has been demonstrated to prevent PP and postpartum mood episodes in women with bipolar disorder.…”
mentioning
confidence: 99%
“…7,8 Women with postpartum psychosis may have a prior history of postpartum psychosis or bipolar disorder, but in some women there is no prior psychiatric history. 11,12 Approximately 25-50% of women with bipolar disorder are at risk of developing postpartum psychosis. 13 ''Postpartum intrusive thoughts'' and ''obsessive compulsive disorder'' commonly occur in women, but with a wide range of severity of symptoms they are concerns for postpartum women.…”
Section: Spectrum Of Diseasementioning
confidence: 99%